ANALISIS PENGARUH KUALITAS PELAYANAN, KEADILAN PELAYANAN DAN KENYAMANAN PELAYANAN TERHADAP HUBUNGAN PERILAKU PELANGGAN SERTA DAMPAK PADA NIAT MEMBELI ULANG - Mertiany Putri Hadrianti; I Made Bayu Dirgantara (JURNAL STUDI MANAJEMEN ORGANISASI, 2019)
This study aims to analyze the effect of service quality, service fairness and service convenience on repurchase intentions, with customer engagement behavior as a mediating variable and make Starbucks Coffee Indonesia the object of this study. The variables used in this study are service quality, service fairness and service convenience as independent variables, customer engagement behavior as mediating variables and repurchase intentions as dependent variables. The research population is customers who have made purchases of Starbucks products at least once. The number of samples used was 130 respondents. This research uses Structural Equation Model (SEM) analysis technique using AMOS 22 analysis tool. The results of this study indicate that service quality has a negative effect on customer engagement behavior, service justice has a positive and significant effect on customer engagement behavior, service convenience has a negative effect on customer engagement behavior and customer engagement behavior has a positive and significant effect on repurchase intentions.